Multidimensional Poverty Analysis : Looking for a Middle Ground - Ferreira, Francisco H.G. (2012)
Widespread agreement that poverty is a multifaceted phenomenon, encompassing deprivations along multiple dimensions, clashes with often vociferous disagreement about how best to measure these deprivations. Drawing on the recent literature, this short note proposes three methodological alternatives to the false dichotomy between scalar indices of multidimensional poverty, on the one hand, and a "dashboard" approach that looks only at marginal distributions, on the other. These alternatives include simple Venn diagrams of the overlap of deprivations across dimensions, multivariate stochastic dominance analysis, and the analysis of copula functions, which capture the extent of interdependency across dimensions. Examples from the literature on both developing and developed countries are provided.